Identification of Cryptosporidiosis in Preschool Children: Identifikasi Cryptosporidiosis pada Anak Usia Prasekolah - Baraa Abdulsalam Hraija Hraija; Dhamyaa Kareem Kadhim; Ghasik Aqeele (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Cryptosporidiosis is a globally distributed parasitic disease that frequently causes diarrheal illness in young children and represents a persistent public health concern. Specific Background: Cryptosporidium parvum is one of the most significant zoonotic protozoa responsible for gastrointestinal infections, and molecular identification methods are increasingly used to clarify epidemiological patterns and genetic diversity of circulating strains. Knowledge Gap: Despite numerous studies on intestinal parasites, molecular data regarding local isolates and subtype distribution of C. parvum in Iraqi children remain limited. Aims: This study aimed to detect C. parvum in diarrheic children using nested polymerase chain reaction targeting the GP60 gene and to analyze the genetic relationships of local isolates through sequencing and phylogenetic analysis. Results: Among 28 fecal samples examined, 12 (42.86%) were positive for C. parvum. Sequencing analysis of positive samples revealed a high genetic similarity (approximately 99%) with global reference strains in the NCBI database, with minimal nucleotide variation. Phylogenetic analysis further classified the detected isolates into two subtype groups, IIc and IIId, with IIc representing the majority of cases. Novelty: This research provides the first molecular confirmation and phylogenetic characterization of these GP60 subtype groups among local Iraqi isolates deposited in the NCBI database. Implications: The findings contribute to the understanding of molecular epidemiology of cryptosporidiosis in Iraq and highlight the importance of expanded genotyping and surveillance studies to clarify transmission pathways and improve disease monitoring. Keywords: Cryptosporidium Parvum, Molecular Epidemiology, Nested PCR, GP60 Gene, Pediatric Diarrhea Key Findings Highlights High proportion of pediatric stool samples contained detectable parasite DNA. Genetic sequencing revealed strong similarity between local isolates and global strains. Two allele groups dominated the detected variants within the sampled population.